Pharmacological potential of 3,5-dimethyl-4-(3-(5-nitrofuran-2-yl)allylidenamino)-1-alkyl-1,2,4-triazolium bromides - A. S. Hotsulia; O. I. Panasenko; T. S. Brytanova (Zaporozhye State Medical University, 2024)
The discovery of new 1,2,4-triazole derivatives offers significant potential for the development of innovative medications. Researchers often favor derivatives of this heterocyclic system due to their ability to create chemical structures with desired pharmacokinetic and pharmacodynamic properties, allowing for targeted effects on specific biological targets. Importantly, biologically active compounds containing triazole have demonstrated relatively low toxicity and minimal risks of mutagenicity. The synergistic combination of these characteristics provides favorable conditions for the development of complex therapeutic effects, ultimately leading to the creation of novel biologically active substances and offering new avenues for the effective treatment of various diseases. Indeed, the utilization of a diverse array of chemical transformations and functionalizations is crucial for obtaining bioactive molecules with desired properties. In this context, 1,2,4-triazole and its derivatives offer a platform for executing a comprehensive range of chemical transformations, thereby enabling the development of compounds with enhanced pharmacokinetic and pharmacodynamic parameters. The aim of the study was to preliminarily assess the possibility of creating a biologically active substance based on 3,5-dimethyl-4-(3-(5-nitrofuran-2-yl)allylidenamino)-1-R-1,2,4-triazole halides. Materials and methods. In silico analysis was used to assess the safety and potential toxicity of the presented compounds, which was implemented using the T.E.S.T. software developed by the US Environmental Protection Agency. SwissADME is an online resource as an effective tool for studying the physicochemical properties and pharmacokinetic parameters of the compounds proposed for study. A molecular docking method that uses a variety of computational algorithms to predict and analyze interactions, including determining the presence of possible binding sites, estimating binding energies, and the spatial arrangement of molecules. The ligand models were created using MarvinSketch 6.3.0, Hyper Chem 8, and AutoDockTools-1.5.6. Discovery Studio 4.0 and AutoDockTools-1.5.6 have been used to prepare the enzymes for analysis. For direct molecular docking, Vina software has been used, which allows predicting and evaluating the interaction between the ligand molecule and the three-dimensional structure of the target protein, taking into account their energy and spatial compatibility. Results. A virtual set of 3,5-dimethyl-4-(3-(5-nitrofuran-2-yl)allylidenamino)-1-alkyl-1,2,4-triazolium bromides was prescreened, which are potential candidates for the further synthesis of biologically active compounds. The general level of toxicity and harmlessness was determined at the predictive level. The key physicochemical characteristics of the molecules have been determined and the general pharmacokinetic parameters have been identified, which allows for a better understanding of their interaction and behavior in the body. The active sites of the model enzymes were analyzed using Vina software, which contributes to a deeper understanding of the interaction of enzymes with their substrates. According to the results of the study, an increased probability of the formation of anti-inflammatory and anticancer properties occurs in 1-alkyl derivatives of 3,5-dimethyl-4-(3-((5-nitrofuran-2-yl)allylidenamino)-1,2,4-triazolium halides with an odd number of Сarbon atoms. Instead, the highest affinity for lanosterol 14α-demethylase has been demonstrated in the studied derivatives with octyl and nonyl substituents, which shows a certain probability of antifungal activity. Conclusions. The prognosis for the creation of a biologically active substance using 1-alkyl derivatives of 3,5-dimethyl-4-(3-(5-nitrofuran-2-yl)allylidenamino)-1,2,4-triazolium halides is quite favorable.